The role of Tai Chi in managing Parkinson's disease: A review of therapeutic mechanisms and clinical outcomes - Adrianna Marta Paziewska; Karolina Jurasz; Radosław Cymer; Ewa Rzeska; Michał Rogulski (Kazimierz Wielki University, 2024)
Tai Chi is a traditional Chinese martial art characterized by maintaining postures and performing slow, fluid movements. This exercise involves actions like extending the knees and hips, shifting weight, flexing, rotating the trunk, and coordinating arm movements. All of this improves balance, motor coordination, and also mental stability. In this review, we explore the relationship between practicing Tai Chi and the improvement of physical abilities in individuals with Parkinson's Disease. We will also compare Tai Chi to other alternative methods for improving physical abilities.